Antiphospholipid Antibodies Modify the Prognostic Value of Baseline Platelet Count for Clinical Outcomes After Ischemic Stroke - Wang, Yinan; Yang, Pinni; Zhu, Zhengbao; Peng, Hao; Bu, Xiaoqing; Xu, Qingyun; Wang, Aili; Chen, Jing; Xu, Tan; Zhang, Yonghong; He, Jiang (Journal of the American Heart Association, 2024)
Antiphospholipid antibodies (aPLs) have been reported to be involved in platelet-mediated thrombosis and inflammation, but the impact on the prognosis of ischemic stroke remains unclear. We aimed to examine whether the association between baseline platelet count (PLT) and long-term clinical outcomes within 2 years after ischemic stroke onset is modulated by aPLs. A total of 2938 patients with ischemic stroke were included in this prospective cohort study. Cox proportional hazards regression models were used to assess the association between the baseline PLT stratified by aPLs status and 2-year clinical outcomes after stroke onset, and an interaction effect between PLT and aPLs on clinical outcomes was tested by likelihood ratio test. There was a significant interaction effect of aPLs and PLT on recurrent stroke ( =0.002) and cardiovascular events ( =0.001) within 2 years after stroke onset. After multivariate adjustment, high PLT was associated with increased risks of recurrent stroke (hazard ratio [HR], 2.78 [95% CI, 1.03-7.45]; =0.039) and cardiovascular events (HR, 2.58 [95% CI, 1.12-5.90]; =0.024) when 2 extreme tertiles were compared among patients with aPL positive, but not among those with aPL negative. The aPLs had a modifying effect on the association between PLT and clinical outcomes within 2 years after ischemic stroke onset. Increased PLT was associated with recurrent stroke and cardiovascular events after ischemic stroke onset among patients with aPL positive, but not in those with aPL negative.